Reliability of Cold Forging Tools. - Engel, Ulf (Wire, 1997)
Tool reliability - a measure of the tool capacity to operate without failure - is an important criterion in the designing and optimization of bulk forming processes taking into account the stochastic nature of tool life. The concept of juxtaposition of load and strength including the combination of numerical process simulation and statistical methods yields an appropriate instrument not only to estimate the reliability but also to identify those primary parameters of influence controlling most significantly the tool life for a given level of confidence.
LFT Import::2019-07-15 (706)